Impact of different organic compost on seed germination and seedling growth performance of mungbean (Vigna radiata) - NAIR, HARITHA THULASEEDHARAN; NATH, GOKUL R; PERUMAL, SIDDHURAJU (The Indian Journal of Agricultural Sciences, 2024)
A better understanding of the physical and biological properties of compost enables us to use the compost wisely in agricultural practices. Besides the bright side of compost on plant growth and soil fertility, immature or unstable compost may be harmful to plants, soil, and soil microorganisms too. Therefore, quality assessment of compost is essential before using it for any type of agricultural activities which will lead to environmentally safe and sustainable farming practices. In the prsent study, compost was used as a substrate for seed germination and not as a fertilizer. So, more investigations must be done in the future to interpret the growth of different crops, their yield and the role of these different composts in it. Using the composts by mixing with soil in different ratios may also give different results, as one of our treatments didn’t show any germination. However, such nutrient-enriched compost materials can appropriately be diluted with a mixture of other organic composts or soil, and further application may provide adequate nutrient sources for crop productivity in the field conditions. This may also reduce the biodegradable waste accumulation in urban and semi-urban vicinity.